2020
DOI: 10.1108/k-09-2019-0632
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationships among knowledge-oriented leadership, knowledge management capacity, innovation performance and organizational performance

Abstract: Purpose Drawing on knowledge-based theory, contingency theory of leadership, social learning theory and resource-based view, this study aims to investigate the relationships among knowledge-oriented leadership (KOL), knowledge management capacity (KMC), innovation performance (IP) and organizational performance (OP). Design/methodology/approach The relationships were examined using the serial mediation model of Hayes (2013). Data were collected from the firms (N = 502) operating in technology development zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 146 publications
6
47
0
Order By: Relevance
“…A higher level of trust creates stronger relationships not only between members of the organization but also between members of the organization and the organization [ 18 ]. The positive relationship of the members of the organization with the organization is expressed by their commitment to the organization, which in the organizational culture perspective is defined as the emotional attachment of the organization members to the organization and identification with the organization’s values, which leads to a member feeling responsibility to help the organization to achieve its goals [ 18 ] empowering their self-efficacy and dedicating themselves to the task [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A higher level of trust creates stronger relationships not only between members of the organization but also between members of the organization and the organization [ 18 ]. The positive relationship of the members of the organization with the organization is expressed by their commitment to the organization, which in the organizational culture perspective is defined as the emotional attachment of the organization members to the organization and identification with the organization’s values, which leads to a member feeling responsibility to help the organization to achieve its goals [ 18 ] empowering their self-efficacy and dedicating themselves to the task [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative analysis of the research revealed that knowledge management activities in an organization are ensured by a transformational leadership style characterized by motivating members of the organization for autonomy, mutual trust and “cultivation” of the commitment to the organization [ 50 , 85 ]. Transformational leaders create a supportive environment and, through charisma and special attention to employees, promote their intellectual development, motivate the creation and sharing of knowledge, develop a learning culture and discipline, and create mechanisms for knowledge management activities [ 17 , 80 , 84 , 86 ].Some authors identify transformational leadership styles with knowledge-oriented leadership, thus emphasizing the importance of this leadership style for ensuring knowledge management activities in an organization [ 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Hayes and Scharkow's (2013) describe that “bootstrap confidence intervals constitute a good approach for detecting path coefficients” (as cited in Cepeda‐Carrion, Cegarra‐Navarro, & Cillo, 2019, p. 81). However, “obtaining bootstrapped confidence intervals for specific indirect effects could be problematic in majority of SEM programs” (Gürlek & Çemberci, 2020, p. 13). For instance, whereas the AMOS provides “bootstrap confidence intervals” for overall indirect effects, it is not possible to obtain “bootstrap confidence intervals” for specific indirect effects (Leth‐Steensen & Gallitto, 2016).…”
Section: Data Analysis and Findingmentioning
confidence: 99%